A Follow-Up Study of Ovarian Cancer (OOPS): A Study Protocol - Gong, Ting-Ting; Liu, Fang-Hua; Liu, Ya-Shu; Yan, Shi; Xu, He-Li; He, Xin-Hui; Wei, Yi-Fan; Qin, Xue; Gao, Song; Zhao, Yu-Hong; Wu, Qi-Jun (Frontiers in Nutrition, 2022)
Introduction Ovarian cancer (OC) is one of the most fatal gynecological malignancies in the worldwide. The five-year survival rate has increased in recent years, however, it was still < 50% in China. Although many prognostic factors of OC, including histotype and stage of disease at diagnosis, have been established, our understanding of modifiable lifestyle factors, such as dietary factors, sleep, physical activity, and so on, in relation to survival after OC diagnosis is still developing. Therefore, the ovarian cancer OC follow-up study (OOPS) is designed to explore the complex relationships between lifestyle factors and OC patient survival. Methods and analysis The OOPS study is an on-going hospital-based large prospective longitudinal cohort study., which established in 2015, and enrolled women aged 18-79 years with a new diagnosis of OC. The aim of OOPS is to assess an association between lifestyle factors and cancer-related outcomes. Data on demographic, clinical information, lifestyle data, and specimens will be collected and analysed. Ethics and dissemination The study was approved by the Institutional Review Board of the Ethics Committee of Shengjing Hospital of China Medical University. We will disseminate our research findings via conference presentations, peer-reviewed publications, and the Internet and social media.